Ductility behaviours of oil palm shell steel fibre-reinforced concrete beams under flexural loading - Yap, Soon Poh; Alengaram, Ubagaram Johnson; Mo, Kim Hung; Jumaat, Mohd Zamin (Taylor & Francis, 2019)
In the effort of developing sustainable concrete, studies on the replacement of conventional coarse aggregates with local waste material are increasing. The new oil palm shell fibre-reinforced concrete (OPSFRC) utilises Malaysia’s waste material and is emerging as a promising sustainable concrete attributed to its lightweight and enhanced concrete properties. In this study, the flexural behaviours of OPSC and OPSFRC beams (with steel fibres.25,.50,.75 and 1.00% by volume) were investigated. The results show that the addition of steel fibres improved both the mechanical properties and moment capacities of OPSFRC specimens. However, the OPSFRC exhibited reduced deflection at failure of about 30–40% relative to the OPSC beams. Meanwhile, the steel fibres significantly improved the failure load to ultimate load ratios of OPSFRC to.65–.80 compared to the ratio of.19 as in OPSC. In addition, different approaches to compute the ductility ratios of OPSFRC beams are also conducted and compared. © 2017, © 2017 Informa UK Limited, trading as Taylor & Francis Group.